Patient acceptability of larval therapy for leg ulcer treatment: a randomised survey to inform the sample size calculation of a randomised trial - Iglesias CP; Spilsbury K; O'Meara S; Petherick ES; Nelson EA; Torgerson DJ (BMC Medical Research Methodology, 2006)
Abstract Background A trial was commissioned to evaluate the effectiveness of larval therapy to debride and heal sloughy and necrotic venous leg ulcers. Larval therapy in the trial was to be delivered in either loose or bagged form. Researchers were concerned that resistance to larval therapy may threaten the feasibility of the trial. Additionally there was concern that the use of larval therapy may require a larger effect size in time to healing than originally proposed by the investigators. Methods To formally evaluate patient preferences a survey using two randomly allocated, nurse administered questionnaires was undertaken. Patients were randomised to receive one of the two following questionnaires (i) preferences between loose larvae and standard treatment (hydrogel) or (ii) patient preferences between bagged larvae and standard therapy (hydrogel). The study was undertaken in a Vascular Clinic, in an Outpatients Department of a large teaching hospital in the North of England. The sample consisted of 35 people aged 18 years and above with at least one leg ulcer of venous or mixed (venous and arterial) aetiology. Results Approximately 25% of participants would not consider the use of larval therapy as an acceptable treatment option for leg ulcers, regardless of the method of containment. For the patients that would consider the use of larval therapy, different preferences in healing times required to use the therapy were observed depending upon the method of containment. The median response of those participants questioned about bagged larvae found that they would be willing to use this therapy even if they were equally able to achieve healing with the use of hydrogel by 20 weeks. For those participants questioned about the use of loose larvae complete healing would have to have taken place over 17 weeks for them to choose larvae as their preferred option rather than hydrogel. This difference was not significant (p = 0.075). Conclusion We found no evidence of widespread resistance to the utilisation of larval therapy from patients regardless of the method of larval therapy containment. These methods have the potential to inform sample size calculations where there are concerns of patient acceptability.